2016
DOI: 10.1021/acs.iecr.6b02862
|View full text |Cite
|
Sign up to set email alerts
|

Performance of an i-SANEX System Based on a Water-Soluble BTP under Continuous Irradiation in a γ-Radiolysis Test Loop

Abstract: The i-SANEX solvent formulation consisting of n ominally 0.2 M TODGA/5% 1octanol/dodecane was g-irradiated under realistic conditions in the INL radiolysis test loop, in contact with both extraction and stripping aqueous phases. The extraction aqueous phase was 4.5 2 M HNO 3 , and the stripping aqueous phase was 0.018 M SO 3-Ph-BTP/0.35 M HNO 3. When irradiated in contact with only the 4.5 M HNO 3 phase, the TODGA solvent maintained excellent extraction performance for americium, cerium, europium and neodymium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 25 publications
4
28
0
Order By: Relevance
“…One of the most relevant ligands, 2,6-bis (5,6-di(sulfophenyl)-1,2,4-triazin-3-yl)pyridine (SO3-Ph-BTP), showed a scarce stability in the homogeneous phase, and an opposite behaviour as a biphasic SO3-Ph-BTP/TODGA system 39,40 . arranged with two triazoles guarantees the selectivity for An, as already outlined in recent publications [41][42][43] .…”
Section: Introductionmentioning
confidence: 99%
“…One of the most relevant ligands, 2,6-bis (5,6-di(sulfophenyl)-1,2,4-triazin-3-yl)pyridine (SO3-Ph-BTP), showed a scarce stability in the homogeneous phase, and an opposite behaviour as a biphasic SO3-Ph-BTP/TODGA system 39,40 . arranged with two triazoles guarantees the selectivity for An, as already outlined in recent publications [41][42][43] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these studies, Peterman et al [12] performed quantitative studies of TODGA samples irradiated in contact with HNO 3 but also in contact with SO 3 -Ph-BTP aqueous phase, in static and in dynamic conditions. They concluded that the stability of TODGA and SO 3 -Ph-BTP, and the general performance of the system depends strongly on the simulation of irradiation process conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Contrariwise to the lipophilic counterpart, poor literature information exists concerning the radiolytic behavior of hydrophilic complexing agents to be used for the MA selective stripping. So far, discordant results have been obtained on the radiation resistance of the non-CHON compliant Bis(di-sulfo-Phenyl)-Triazine-Pyridine (SO3-Ph-BTP), former i-SANEX reference hydrophilic ligand for MA back-extraction [38][39].…”
Section: Introductionmentioning
confidence: 99%